Single and Binary CO2/CH4 Separation of a Zeolitic Imidazolate Framework-8 Membrane - Lai, L.S. (Wiley-VCH Verlag, 2017)
The performance of a zeolitic imidazolate framework-8 (ZIF-8) membrane in single and binary CO2/CH4 gas separation was investigated by means of a gas transport model that included generalized Maxwell-Stefan and binary friction models. The model concerns gas diffusion through the membrane layer, gas flow through membrane intercrystalline pores, and resistance of the support layer. The effective membrane area considering the actual area for the gas permeated through the membrane was also introduced in this model. The selective ZIF-8 membrane was successfully synthesized using a microwave-assisted solvothermal method on an α-alumina support pre-attached with ZIF-8 seeds by solvent evaporation. The simulated data agreed well with the experimental data. The model revealed that the membrane intercrystalline pores and its effective area significantly affected the CO2/CH4 gas permeation and separation performance. © 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim